STORYTELLING FOR EMOTIONAL DEVELOPMENT: THE IMPLEMENTATION OF STORYTELLING ACTIVITIES AS TEACHERS’ EFFORTS TO FOSTER EMOTIONAL MATURITY IN CHILDREN AGED 5–6 YEARS - Tito Parta Wibowo Tito; Ani sumarni; Nuryati (Cakrawala Pedagogik, 2026)
Abstract This study aims to explore and comprehensively describe the efforts of teachers in fostering emotional maturity in children aged 5–6 years through storytelling activities at PAUD BKB Kemas Iqro. Emotional maturity is a critical foundation in early childhood personality development, encompassing the ability to recognize and understand one’s own emotions and those of others, express feelings appropriately, and regulate emotional responses in various social contexts. A descriptive qualitative method was employed, using observation, in-depth interviews with teachers, and documentation of learning activities. Twenty children from Group B participated in this research. The findings reveal that well-structured, varied, and interactive storytelling sessions encourage children to express their emotions more openly, enhance empathy, and develop better self-control. Teachers play a central role in this process, acting as facilitators, emotional companions, and role models in expressing feelings in a healthy manner. The selection of stories that resonate with children's daily experiences, combined with techniques such as reflective questioning and facial expression modeling, serve as key contributing factors. This study concludes that storytelling is not only a medium for literacy development but also an effective educational tool to support the growth of emotional maturity in early childhood.